Analisis Manajemen Proyek Menggunakan Metode CPM dan PERT pada Proyek Instalasi Pipa di PT. XYZ - Elfandani, Moh Alviko; Said Salim Dahda (Journal of Management and Bussines (JOMB), 2026)
This study aims to analyze the management of a pipeline installation project at PT. XYZ and determine the critical path and estimated project duration using the Critical Path Method and the Project Evaluation and Review Technique. The research method used is quantitative descriptive, with data collected through direct observation of project activities in the field and ongoing project schedule documents. The collected data includes the sequence of activities, the duration of each activity, and dependencies between activities. These data are then analyzed using an Activity on Node network diagram, calculations of earliest start and finish times, latest start and finish times, total float, and estimated expected duration using the Project Evaluation and Review Technique. The results indicate that the project's critical path lies in the activities of Fit-Up/Erection, Welding Joint, Install Gasket, Install Pump, Fabrication and Install Support, and Test Package, with a total project duration of 144 days according to the Critical Path Method and 142.4 days according to the Project Evaluation and Review Technique, with a probability of on-time project completion of 72.24 percent. In conclusion, the application of the Critical Path Method and the Project Evaluation and Review Technique (P&R) can accelerate the project duration compared to the initial planned schedule of one hundred and eighty-six days. The P&R provides a more realistic time estimate by considering the uncertainty of activity durations. To accelerate project completion, it is recommended to add resources to critical activities and conduct regular project progress evaluations to ensure proper monitoring of the critical path.   Keywords: Project Management, Critical Path, Pipe Installation